Effects Of Brand Image, Rate Of Profit-Sharing Ratio, Contract Application, And Trust On The Customers’ Decision To Save At Islamic Banks - Rizkina, Erika; Adha, Mufti Alam; Wijaya, Andy Putra (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2024)
The rapid development of Islamic bank has resulted in business competition. This study analyzes the influences of brand image, rate of profit-sharing ratio, contract application, and trust on customers’ decision to save at Islamic banks. The all Islamic banks in Yogyakarta City are the objects in this study, this study uses a questionnaire to collect as many as 100 respondents as the samples, that is, the customers of Islamic banks. This study uses the quantitative method with multiple linear regression analysis. The study shows that brand image positively and significantly influences the customers’ decision to save at Islamic banks, with a value of 0.00 < 0.05. The Rate of profit-sharing ratio positively and significantly affects the customers’ decision to save at Islamic banks, with a value of 0.02 < 0.05. The contract application positively and significantly influences the customers’ decision to save at Islamic banks, with a value of 0.05. Trust positively and significantly impacts the customers’ decision to save at Islamic banks, with a value of 0.02 < 0.05. Simultaneously, brand image, rate of profit-sharing ratio, contract application, and trust positively and significantly influence the customers’ decision to save at Islamic banks.